Improving Students' Mathematical Understanding Ability Through Canva Assisted Problem-Based Learning Model on Straight Line Equations - Nurfalah, Ilma; Supardi, Alfi Fani; Al Mawaddah, Azkia Mudrikah; Silviani, Rina; Sunaryo, Pranestya Rachmaeny; Hutajulu, Masta (Al-Khawarizmi, 2023)
This study aims to determine whether there is an increase in students' mathematical understanding if learning is carried out using the scientific method compared to problem-based learning methods on straight line equations material. This research was conducted at SMP Negeri 5 Cimahi. This study uses a quantitative and descriptive qualitative approach. Learning outcomes data is used as a parameter to measure the increase in mathematical understanding ability. The results showed an increase in students' mathematical understanding abilities when learning using problem-based learning methods increased by 18% compared to scientific methods.